Mangkunegaran dance style in the custom and tradition of Pura Mangkunegaran (Harmonia: Journal of Arts Research and Education, 2017)
Mangkunagaran dance style is regarded as a cultural identity that is highly upheld by Mangkunagaran’s society. In the organization that lives in Mangkunagaran, the sustainability of Mangkunagaran dance style is protected by the special art institution namely Langen Praja, under a bigger organization in Mangkunagaran namely Reksa Budaya. The existence of Mangkunagaran dance style is in fact related to the custom and tradition in Pura Mangkunagaran. The aim of this research is to find out how Mangkunagaran dance style is and what kind of roles that Mangkunagaran dance style has that may influence the custom and tradition in Pura Mangkunagaran. Methods used in this research is qualitative. Techniques of data collection used were observation, interview, and documentation study and the data validity technique implemented was data triangulation. Meanwhile, the data was analysed by using text analysis towards the Mangkunagaran dance style and the context analysis towards the role of Mangkunagaran dance in the custom and tradition had by Pura Mangkunagaran.